1981
DOI: 10.1007/bf00154889
|View full text |Cite
|
Sign up to set email alerts
|

The academic department as environment for teaching and learning

Abstract: This study reviews the literature on academic environments with particular reference to the academic department which is seen as the most important factor in the teaching and learning environment. Departmental environment characteristics as identified by faculty and by students are described. For students the most important are:--Student-Faculty Relationships;-Interest and Engagement in Teaching; and -Satisfaction with Instruction. Differences between teaching and between learning environments are explained, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1983
1983
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…For example, generally science disciplines place more emphasis on research and grantsmanship and less emphasis on teaching and learning than do the humanities and social sciences. They also offer course environments that frequently emphasize memorization, particularly in introductory courses; are less welcoming to students; and less encouraging of student learning (Biglan, 1973b;Tobias, 1992;Volkwein, 1991;Winteler, 1981). On the other hand, there is far greater paradigmatic uniformity and agreement on fundamental concepts in the sciences than other disciplines.…”
Section: Disciplinary Characteristicsmentioning
confidence: 95%
“…For example, generally science disciplines place more emphasis on research and grantsmanship and less emphasis on teaching and learning than do the humanities and social sciences. They also offer course environments that frequently emphasize memorization, particularly in introductory courses; are less welcoming to students; and less encouraging of student learning (Biglan, 1973b;Tobias, 1992;Volkwein, 1991;Winteler, 1981). On the other hand, there is far greater paradigmatic uniformity and agreement on fundamental concepts in the sciences than other disciplines.…”
Section: Disciplinary Characteristicsmentioning
confidence: 95%
“…Thus, the bivariate relationship between performance and 'dissatisfiers" may imply that students' performance was associated with only those factors that are visible about the academic programme, that is, the number of quality faculty that interacts with the student in and out of class, students having sufficient time for independent study, and availability of elective courses that could be beneficial to the student. Indeed, studies have shown that the college environment has great influence on both the cognitive and affective outcomes of the students (Winteler, 1981;Terenzini, Theophilides & Lorang, 1984). It is crucial therefore, that the Nigerian university system strives to have high quality and experienced faculty in its academic programme, and design and structure the programme to provide students with sufficient opportunity to engage in independent study.…”
Section: Educational Importancementioning
confidence: 99%